The Effects of Allopurinol on Levels of Cardiac Troponin Following Non-ST Elevation Myocardial Infarction: A Pilot Randomized Clinical Trial - Sajad Khiali; Parvin Sarbakhsh; Sina Mashayekhi; Elham Mohamadrezapour; Samaneh Dousti; Taher Entezari-Maleki (Pharmaceutical Sciences, 2021)
Background: Given the potential anti-ischemic effects of allopurinol, we aimed to assess whether allopurinol administration may reduce myocardial injury following non-ST elevation myocardial infarction (NSTEMI). Methods: A randomized clinical trial (RCT) was conducted on 100 individuals with NSTEMI.The intervention group (n=50) received 600 mg oral allopurinol at the time of diagnosis ofNSTEMI, followed by 300 mg every day for two next days and the standard treatment of NSTEMI, while the control group (n=50) received only the standard treatment. Serum concentrations of cardiac troponin I (cTnI) were measured at baseline, and 8, 16, 24, and 32 hours after the treatment. Results: The baseline demographic and clinical data of the patients were not statistically different between the intervention and control groups (all P > 0.05). The comparing estimated marginal mean ± standard error for cardiac troponin I (cTnI) levels revealed no significant difference between the study groups (2.93 ± 0.27, 2.25 ± 0.27; P=0.082). The linear mixed model results showed that the interaction of time and group was not statistically different (P=0.751). Moreover, there was a decreasing trend over time for cTnI in both groups (P=0.039). Conclusion: The present pilot RCT did not support the potential cardio-protective benefits of allopurinol administration on decreasing myocardial injury following NSTEMI.